2023
DOI: 10.1007/s00018-022-04671-x
|View full text |Cite
|
Sign up to set email alerts
|

ABC-transporter CFTR folds with high fidelity through a modular, stepwise pathway

Abstract: The question how proteins fold is especially pointed for large multi-domain, multi-spanning membrane proteins with complex topologies. We have uncovered the sequence of events that encompass proper folding of the ABC transporter CFTR in live cells by combining kinetic radiolabeling with protease-susceptibility assays. We found that CFTR folds in two clearly distinct stages. The first, co-translational, stage involves folding of the 2 transmembrane domains TMD1 and TMD2, plus one nucleotide-binding domain, NBD1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 93 publications
(189 reference statements)
0
22
0
Order By: Relevance
“…This process is dependent on the interaction between COPII proteins with specific positive export signals, with the better characterized motif for CFTR being the diacidic code Asp565-Ala566-Asp567 (DAD), which is located in NBD1 ( Nishimura and Balch, 1997 ). This motif acts as a positive cargo signal required for Sec24-mediated COPII packaging into the vesicles ( Nishimura and Balch, 1997 ), while its disruption has been shown to decrease both association with Sec24 and exit from the ER ( Wang et al, 2004 ) and complete abrogation has been shown to prevent CFTR processing ( Farinha et al, 2013 ) while also partially affecting its folding ( Im et al, 2023 ). By successfully overcoming the ERQC CFTR is finally packed into COPII coated vesicles to traffic firstly to the ERGIC and then to the Golgi apparatus.…”
Section: Cftr Traffickingmentioning
confidence: 99%
“…This process is dependent on the interaction between COPII proteins with specific positive export signals, with the better characterized motif for CFTR being the diacidic code Asp565-Ala566-Asp567 (DAD), which is located in NBD1 ( Nishimura and Balch, 1997 ). This motif acts as a positive cargo signal required for Sec24-mediated COPII packaging into the vesicles ( Nishimura and Balch, 1997 ), while its disruption has been shown to decrease both association with Sec24 and exit from the ER ( Wang et al, 2004 ) and complete abrogation has been shown to prevent CFTR processing ( Farinha et al, 2013 ) while also partially affecting its folding ( Im et al, 2023 ). By successfully overcoming the ERQC CFTR is finally packed into COPII coated vesicles to traffic firstly to the ERGIC and then to the Golgi apparatus.…”
Section: Cftr Traffickingmentioning
confidence: 99%
“…23 A recent study suggests CFTR folds in two stages: first TMD1, TMD2, and NBD1 and second NBD2 and the association of TMDs with NBDs. 24 TMD1 begins with an N-terminal region called the lasso motif that contains a membrane bound helix wrapped around TMD2 at TH10 and TH11 and two aliphatic helices half submerged on the cytosolic side of the membrane 25 (Figure 2A). The lasso motif is unique to the ABCC subfamily of transporters and is present in CFTR and Multidrug resistant transporter (MR1−9).…”
Section: Cftr Structurementioning
confidence: 99%
“…TMD1/2 association may undergo the greatest post-translational conformational change alongside the post-translational folding of NBD2 . A recent study suggests CFTR folds in two stages: first TMD1, TMD2, and NBD1 and second NBD2 and the association of TMDs with NBDs …”
Section: Cftr Structurementioning
confidence: 99%
“…Using cryo-EM structures of chaperone complexes and glucocorticoid receptor (GR) as a model client, they described the mechanisms of a complete chaperone cycle involving Hsp90, Hsp70, and selected cochaperones (Noddings et al 2023 ; Noddings et al 2022 ; Wang et al 2022 ). Ineke Braakman (Utrecht University, Netherlands) discussed the role of the Hsp90 complex as a triage system for mutant CFTR function, showing that specific domain mutants give rise to the most profound folding defects which influences chaperone interactions (Im et al 2023 ).…”
Section: Hsp90 Interactions With Cochaperones Chaperones and Client P...mentioning
confidence: 99%